OVERVIEW OF THE UNIQUE HEALTH SYSTEM (SUS): : AN APPROACH TO BASIC CARE - Cristina Ribeiro Akamine, Suellen (Health and Society, 2021)
The Unified Health System has a network of teaching and research institutions such as universities, institutes and schools of public health that interact with state and municipal secretariats, the ministry of health, agencies and foundations. Primary Care is the main gateway to the SUS, starting with welcoming, listening and offering solutions to most health problems of the population, minimizing damage and suffering, aiming at the effectiveness of care, ensuring its completeness. SUS offers users the Hospital Care service of medium and high complexity. The objective of this study was to emphasize the importance of organizing the Unified Health System, highlighting Primary Care, Family Health Strategy and NASF, aiming at preventing health problems for the population. The results observed through bibliographic studies were the importance of adopting prevention strategies to minimize or avoid the individual’s illness. It was concluded that the organization of the health system from Primary Care to Hospital Care is extremely important, emphasizing the need to seek preventive strategies adopted by the teams to prevent diseases, minimizing the need for hospital admissions, and providing quality of life to population.